2015
DOI: 10.1111/all.12627
|View full text |Cite
|
Sign up to set email alerts
|

Th2 cytokines impair innate immune responses to rhinovirus in respiratory epithelial cells

Abstract: (word count: 246245) 1Background: Asthma and other Th2 inflammatory conditions have been associated with increased 2 susceptibility to viral infections. The mechanisms by which Th2 cytokines can influence immune 3 responses to infections are largely unknown. 4 Methods:We measured the effects of Th2 cytokines (IL-4 and IL-13) on bronchial epithelial cell 5 innate immune antiviral responses by assessing interferon (IFN-β and IFN-λ1) induction following 6 rhinovirus (RV)-16 infection. We also investigated the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
124
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 41 publications
6
124
0
6
Order By: Relevance
“…This study is consistent with other studies showing that Th2 cytokines and transforming growth factor-b are able to suppress rhinovirus-induced IFN production and augment virus replication in bronchial epithelial cells (17,18) and fibroblasts (19). These studies did not investigate nuclear SOCS1 expression, so the mechanism(s) through which Th2 cytokines/transforming growth factor-b suppressed IFN induction are not known.…”
supporting
confidence: 92%
“…This study is consistent with other studies showing that Th2 cytokines and transforming growth factor-b are able to suppress rhinovirus-induced IFN production and augment virus replication in bronchial epithelial cells (17,18) and fibroblasts (19). These studies did not investigate nuclear SOCS1 expression, so the mechanism(s) through which Th2 cytokines/transforming growth factor-b suppressed IFN induction are not known.…”
supporting
confidence: 92%
“…First, the majority of asthmatics ( particularly those with childhood-onset asthma) are atopic [15], and studies of birth cohorts have demonstrated a greatly increased risk of diagnosed asthma and AHR in atopic children [16], particularly those sensitised to house dust mite (HDM), cats and dogs [17]. Second, the presence of airway allergic inflammation predisposes children to rhinovirus-induced recurrent wheezing and asthma exacerbations [18], and this interaction between allergic sensitisation and virus exposure predisposes to the development of asthma in childhood [19], possibly through an effect of type-2 cytokines (such as interleukin (IL)-4 and IL-13) on the innate immune responses to airway viral infection [20]. Third, seasonal asthma, associated with specific environmental allergen exposure, is a well-described clinical entity [21].…”
Section: Environmental Allergens As a Cause Of Asthmamentioning
confidence: 99%
“…Some studies did not observe such IFN-b deficiency (4-7). Yet, others report either intrinsic impairment of the IFN-b response to respiratory viruses (6,(8)(9)(10)(11) or negative modulation of this response by pathologic factors associated with diseased airways (12)(13)(14)(15)(16). Importantly, stimulation of IFN-b production or exogenous supplementation of this cytokine facilitates virus clearance even in cells with normal IFN-b responses (5,17,18).…”
mentioning
confidence: 99%